Peningkatan Kualitas Pembelajaran melalui Optimalisasi Laboratorium Virtual untuk Mendukung Pendidikan Adaptif dan Berkelanjutan di Sekolah Dasar - Rosmiati; Amelia Widya Hanindita; Zukhruf Annisa Zalzabila; Dionisius Ronaldino Fernandes Dugis (Universitas PGRI Adi Buana Surabaya, 2026)
Educational transformation in the digital era requires elementary school teachers to integrate technology effectively into science instruction. Limited laboratory facilities, insufficient experience in using virtual laboratories, and suboptimal teacher competencies remain significant challenges in implementing inquiry- and practicum-based learning. This community service program aimed to enhance elementary school teachers' competencies in optimizing virtual laboratories to support adaptive and sustainable science learning. The program was organized by the Elementary School Teacher Education Study Program, Universitas PGRI Adi Buana Surabaya, in collaboration with the Indonesian Teachers Association (PGRI) of Gondang District, Mojokerto Regency, from 13 to 19 June 2026, involving 35 elementary school teachers. The program employed a Participatory Action Research (PAR) approach consisting of five stages: needs analysis, training, mentoring in instructional material development, implementation, monitoring, and evaluation. The needs analysis revealed that 94.3% of teachers were ready to implement virtual laboratories, 91.4% required mentoring, 88.6% needed training, and 77.1% had never used virtual laboratories. Program evaluation demonstrated a significant improvement in teachers' understanding, with the average score increasing from 61.8 in the pre-test to 87.6 in the post-test, representing a 25.8-point gain. Furthermore, 91.4% of teachers were able to operate virtual laboratory platforms independently, 94.3% successfully developed teaching modules aligned with the Merdeka Curriculum, and 88.6% effectively integrated virtual laboratories into classroom instruction. Classroom implementation also increased students' active participation and strengthened teachers' ability to facilitate technology-enhanced learning. Overall, the program effectively improved teachers' professional competencies, enhanced the quality of science education, and supported the development of adaptive and innovative.